Modernization without development : Thailand as an Asian case study - Jacobs, Norman (New York, Praeger Publishers, 1971)
This is case study of development problems facing Thailand. It includes topics like: the theory and structure of authority; general considerations of economy; patrimonialism and economic development; occupation; stratification; kinship and descent; religious brotherhood; religious values and society; and integration, stability; and legitimate change.
Includes bibliographical references: p. 397-420.
lje 16/05/2018
Loans
Keywords: Economic history; Economic development; Thailand; Thailand